The ovarian stroma as a new frontier. Issue 3 (September 2020) - Kinnear, Hadrian M; Tomaszewski, Claire E; Chang, Faith L; Moravek, Molly B; Xu, Min; Padmanabhan, Vasantha; Shikanov, Ariella
Abstract : Historically, research in ovarian biology has focused on folliculogenesis, but recently the ovarian stroma has become an exciting new frontier for research, holding critical keys to understanding complex ovarian dynamics. Ovarian follicles, which are the functional units of the ovary, comprise the ovarian parenchyma, while the ovarian stroma thus refers to the inverse or the components of the ovary that are not ovarian follicles . The ovarian stroma includes more general components such as immune cells, blood vessels, nerves, and lymphatic vessels, as well as ovary-specific components including ovarian surface epithelium, tunica albuginea, intraovarian rete ovarii, hilar cells, stem cells, and a majority of incompletely characterized stromal cells including the fibroblast-like, spindle-shaped, and interstitial cells. The stroma also includes ovarian extracellular matrix components. This review combines foundational and emerging scholarship regarding the structures and roles of the different components of the ovarian stroma in normal physiology. This is followed by a discussion of key areas for further research regarding the ovarian stroma, including elucidating theca cell origins, understanding stromal cell hormone production and responsiveness, investigating pathological conditions such as polycystic ovary syndrome (PCOS), developing artificial ovary technology, and using technological advances to further delineate the multiple stromal cell types.